2018
DOI: 10.1111/ijd.14068
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in adult patients with nonmelanoma skin cancer in Cape Town, South Africa: a cross‐sectional study

Abstract: The findings highlight the need for the development of recommendations and guidelines on sun protection in patients with NMSC, while still ensuring an adequate vitamin D status. High risk factors included winter and female gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, after the diagnosis, half of the patients still did not use SPF. The results are similar to that of a study in South Africa where 83% of the participants who presented themselves for a first non-melanoma skin cancer and 50% of the cases with previous non-melanoma skin cancer did not use sunscreen (44).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, after the diagnosis, half of the patients still did not use SPF. The results are similar to that of a study in South Africa where 83% of the participants who presented themselves for a first non-melanoma skin cancer and 50% of the cases with previous non-melanoma skin cancer did not use sunscreen (44).…”
Section: Discussionsupporting
confidence: 88%
“…Season also has an influence even closer to the Equator, at 33˚S, in South Africa, ~50% of the patients with BCC and/or squamous cell carcinoma had levels below 20 ng/ml, and over 90% were below 30 ng/ml, also having a considerable seasonal variation (44).…”
Section: Discussionmentioning
confidence: 99%
“…As stated in the previous sections that there are few published works linking vitamin D levels and NMSC, with inconsistent results (Asgari et al, 2010;Caini et al, 2014;Eide et al, 2011;Liang et al, 2012;Soares et al, 2018;Tang et al, 2011;Tang et al, 2010;van Dam et al, 2000;van der Pols et al, 2013;van Deventer, Kannenberg & du Toit, 2018;Vojdeman et al, 2019). We consider this to be a limitation for our study since we cannot design it from a more generalized hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies suggest that vitamin D and its metabolites may reduce the risk of skin cancer. However, only a few epidemiological studies have assessed the association between vitamin D serum levels and NMSC risk, and these have shown controversial results: some report an association between higher vitamin D levels and an increased risk of developing skin cancer (Asgari et al, 2010;Eide et al, 2011;Liang et al, 2012;Soares et al, 2018;van der Pols et al, 2013;Vojdeman et al, 2019), while others report a decreased risk (Tang et al, 2011;Tang et al, 2010), and others found no association (van Dam et al, 2000;van Deventer, Kannenberg & du Toit, 2018). In 2014, Caini et al (2014 found a statistically significant positive association with an increased risk of NMSC for high values of 25(OH)D 3 in their review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a case–control study, vitamin D and SCC risk were directly associated in the unadjusted model but after correcting for the effect of undesired variables (including age, sex and sunlight exposure) there was no significant association [ 56 ]. Perhaps, the association between high vitamin D levels and SCC suggests that UV exposure may have a predominant adverse influence that exceeds any putative benefit from the higher levels of vitamin D. What is clear is that sun protection should always be advised, especially for patients with skin cancer, while ensuring adequate levels of vitamin D [ 57 ]. Hormone receptors are also important in both AK and SCC.…”
Section: Influential Role Of Exposome Factorsmentioning
confidence: 99%